Secularism : the hidden origins of disbelief - King, Mike, 1953- (James Clarke & Co., 2007)
Spirituality is a difficult subject in the modern world. Everywhere, from popular media to the university, from the bookshelf to the dinner table, religions are derided or marginalised and public figures, such as Richard Dawkins, set upon anyone who admits to a belief in God. It seems that science and religion are fundamentally at odds and that a mutual respect is unacceptable to either in their parallel pursuit of 'truth'. Yet the majority of Enlightenment authors engaged with both science and spirituality and did not lose their faith. Today we tend to see these authors as not having applied.